Analysis of NbN thin film deposition by plasma-enhanced ALD for gate electrode application - Hinz, J.; Bauer, A. J.; Frey, Lothar (Semiconductor Science and Technology, 2010)
NbN thin films have been deposited by plasma-enhanced atomic layer deposition (PEALD) from the metal organic precursor Nb(N-t-Bu)(NMeEt)(3) (TBTMEN). The substrate was covered with a precursor monolayer and was then exposed to a plasma for a sufficient duration to form NbN x. This cycle was repeated to grow a film of several nanometres. From film analysis by spectroscopic ellipsometry, four-point probe measurement and x-ray photoelectron spectroscopy, data on growth rate, resistivity and composition are presented. The deposition parameters were adjusted in order to obtain films with a homogenous film thickness and resistivity. Lowering of the plasma pressure reduced the specific resistance of the Nb films. The nitrogen content could be varied by admixing nitrogen into the plasma, and thereby for the first time a low resistivity ALD film containing the stoichiometric carbon-free NbN phase was obtained. Furthermore, the cycle period could be reduced by increasing the deposition temperature. Compared to other deposition methods, PEALD was shown to be an excellent method for the fabrication of low-resistivity metallic films at a reduced process temperature. For the measurement of the film thickness by spectroscopic ellipsometry, a model for the complex dielectric function was set up and was related to the electronic structure and the resistivity of the films.